The Effect of GeoGebra-Assisted Problem-Based Learning on Students’ Mathematical Literacy Skills and Learning Motivation - Mayang Purbaningrum; Ali Mahmudi (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study aimed to examine the effect of GeoGebra-assisted problem-based learning on vocational high school students’ mathematical literacy and learning motivation. Thirty-three students of one chemical industry class in grade 11 of vocational high school were chosen as the subjects for this study period. Simple random sampling was employed for the sampling process. This study was quantitative research and used a quasi-experimental design in the form of one-group pretest-posttest design. In this study, tests, questionnaires, and documentation were used as data collection methods. Descriptive and inferential analyses using paired sample t-tests were performed on the test data. In the study's findings, mathematical literacy students got a p-value of 0.000 0.05 as a significant level, and learning motivation students got a p-value of 0.006 0.05 as a significant level, indicating a difference between the study's average before and after treatment. Because p-value 0.05, H0 is rejected. So, there is an average difference between the two test results. Based on those results, GeoGebra-assisted problem-based learning affects mathematical literacy and learning motivation of vocational high school students on financial mathematics material. Teachers can use Geogebra as one of the media that can develop students' mathematical literacy and learning motivation.